Revising Arabic Grammar Studies Critical Reporting and Analysis of the Book of Asul al-Tafkir al-Nahwi - Hadi Rezvan (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Contrary to many studies in the field of Arabic Grammar, Ali Abu al-Makarem’s research has a special place. In his works, he has attempted to study the history of Arabic Grammar by a methodological study in a general and comprehensive way. One of his most important books is “Asul al-Tafkir al-Nahwi” where the author talks about the difficulties facing Arabic Grammar studies. He sought to identify both positive and negative elements by reconstructing classical methods of Arabic Grammar studies. The author of this article, by a comprehensive study of this book, seeks to find an answer to the following questions: What are the most important general principles on which his research is based? What does Grammatical Induction mean in author’s opinion? What steps has the concept of analogy gone through in the history of Arabic Grammar? What is the position of Justification or Explanation and Interpretation in principles of Arabic Grammar ? And what is the impact of correctly recognizing these concepts in Arabic language research and teaching? This paper studies the various chapters and titles of the book to answer such questions, according to the descriptive-analytical methodology.